Pertanggungjawaban Hukum oleh Bank Kepada Nasabah atas Kelalaian dalam Penerapan Prinsip Kehati-Hatian Bank (Prudential Banking Principle) dalam Pembukuaan Buku Rekening - Dinda Maudina; Ery Agus Priyono (Universitas Batanghari Jambi, 2023)
Banking is one of the financial institutions that is worthy of a strategy in the country's economy, both in harmony and economic development as well as in national development. The banking world has a very important role for customers in depositing funds from the customer and borrowing funds from the bank, this is because the customer is one of the factors that have an important role in a banking business. So that to obtain these customers, it is also necessary to have the trust that can be given by the bank to its customers. The precautionary principle is the principle which states that the bank is obliged to implement it in carrying out operations and business activities. To protect public funds, it is very necessary that the precautionary principle entrusted to him, one of which is in the opening of the account book. This research method is a type of library research using a juridical-normative approach. The result of the research is that the responsibilities of bank employees are divided into criminal responsibility, administrative responsibility, and civil responsibility. The responsibility for opening a bank account with the precautionary principle begins with the application for opening a bank account. Next, fill in the data according to the original identity of the prospective customer, then confirm whether the data entered is completely correct, or not. If it has been continued with the provision of account numbers and savings as well as Automated Teller Machines (ATM) and initial deposit. If it is not correct, then wait until the prospective customer can provide a correct and valid identity. Confirmation which is a form of application of the prudential banking principle